Health-Promoting Effects of Serial vs. Integrated Combined Strength and Aerobic Training - Karatrantou, K.; Gerodimos, V.; Häkkinen, K.; Zafeiridis, A. (International Journal of Sports Medicine, 2017)
Combined strength and aerobic training programs are widely used for improving markers of physical fitness and health. We compared the efficiency of a serial and an integrated combined training program on health and overall fitness in middle-aged females. 54 females (46.7±4.5yrs) were assigned to a serial (SCG) or an integrated (ICG) combined training group or to a control group (CG). The SCG and ICG performed a 3-month training combining aerobic dance and calisthenics. The 2 training programs differ in the sequence of aerobic and strength exercises. SCG performed the strength exercises prior to aerobic; in ICG, the aerobic and strength exercises were altered in a predetermined order. Body composition/circumferences, blood pressure, respiratory function, flexibility, balance, muscle strength/endurance, power and aerobic capacity were measured before and after training. SCG and ICG significantly increased muscle strength and endurance, power, aerobic capacity, flexibility, balance, fat-free mass and respiratory function (p<0.001–0.05), while significant reductions were observed for blood pressure, heart rate and body fat/circumferences (p<0.001–0.05). However, there were no significant differences between SCG and ICG after training. Serial and integrated combined training programs confer analogous adaptations and can be used interchangeably for counteracting the detrimental effects of sedentary lifestyle on indices of physical fitness and health.
Keywords: health; concurrent training; aerobic dance; calisthenics; cardiovascular adaptations; neuromuscular adaptations